DETERMINAN PERJANJIAN UTANG BERBASIS AKUNTANSI (ACCOUNTING - BASED COVENANT) PADA OBLIGASI YANG DITERBITKAN OLEH PERUSAHAAN YANG TERDAFTAR INDEKS KOMPAS 100 - Nurabiah Nurabiah; Herlina Pusparini; Alamsyah Alamsyah; Nur Fitriyah; Isnawati Isnawati (Valid: Jurnal Ilmiah, 2018)
The objective of this study is to examine the influence of maturity, collateral, firm size, profitability, leverage, spread, firm reputation, and bond quality toward the accounting-based convenant. The sample of this study was index kompas 100 during the period of 2014- 2016, so that sample total is 114. This research was conducted based on documentation, while data is acquired through the Indonesian Capital Market Directory (ICMD) and Indonesia Stock Exchange (IDX) Fact. Data were analyzed based on multiple linear regression, and t-test using the e-views. The results of the analysis in this study indicate that the collateral spread,firm reputation and bond quality, have significant influence on the accounting-based convenant while maturity, firm size profitability, and leverage does not